Sahih Muslim: being traditions of sayings and doings of the prophet Muhammad AS narrated by his companions and compalied under the title al Jami'us Sahih - Imam Muslim (Dar El Fiker, 1993)
tr, jil.1=c.1,ws,jl.1.c.2,jl.2-4.c.1; sn,jl.1,c.3; jl.2,c.2; ,jl.3,c.2-3;/tr, jil.2=c.3; jil.4=c.2/ws.jl.3.c.4